Operando monitoring of metal sites and coke evolution during non-oxidative and oxidative ethanol steam reforming over Ni and NiCu ex-hydrotalcite catalysts - Passos, Aline Ribeiro [UNESP]; Pulcinelli, Sandra Helena [UNESP]; Santilli, Celso Valentim [UNESP]; Briois, Valérie (Elsevier, 2019)
Ni and NiCu bimetallic catalysts derived from hydrotalcite-like compounds have been studied by operando time-resolved X-ray Absorption Spectroscopy/Raman Spectroscopy/Mass Spectrometry during ethanol steam reforming (ESR) reaction followed by oxidative regeneration and also during oxidative ethanol steam reforming (OSR) reaction. The presence of copper in the NiCu bimetallic catalyst enhanced nickel reducibility, promoted higher H2 production and mitigated the deposition of graphitic carbon. Carbon deposition evidenced by Raman was the main cause of the catalyst deactivation. Exposure to O2/He atmosphere allowed the regeneration of spent catalysts by burning coke deposits, and also, contributed to improve the nickel redispersion on alumina. Differently to the conventional reactivation, which requires further reductive treatment for recovering active metallic species, H2 produced after regeneration under ESR conditions promoted the self-reactivation of the catalyst and restored the activity at 98% of ethanol conversion. The addition of O2 to the ethanol/water feed in the OSR decreased the amount of deposited filamentous-like coke but also the selectivity to H2.
Keywords: Catalyst regeneration; Coke deposition; Ethanol steam reforming; Nickel-copper catalyst; Oxidative ethanol reforming; Raman; XAS